Retrovirus-like particles from the human T47D cell line are related to mouse mammary tumour virus and are of human endogenous origin - Faff, O.; Murray, A. B.; Schmidt, J.; Leib-Mösch, C.; Erfle, V.; Hehlmann, R. (Journal of General Virology, 1992)
Retrovirus-like particles were secreted in a steroid-dependent manner by the human mammary carcinoma cell line T47D. The particles exhibited typical retroviral properties such as their electron microscopic appearance (95 nm in diameter) and occasional budding, sedimentation at 1.14 g/ml, reverse transcriptase activity and genomic RNA. The T47D particles were related to mouse mammary tumour virus (MMTV) as shown by their ultrastructural appearance (B type-like eccentric dense cores and budding), Mg2+ dependence of the reverse transcriptase activity; immunological reactivity with MMTV-directed antibodies (revealing proteins of 63K, 52K, 26K and 18K), and hybridization of particle RNA with MMTV DNA under stringent conditions. Purified particles were able to incorporate deoxynucleoside triphosphates in the absence of an exogenous primer and template, thus indicating the existence of a complete and biochemically functional reverse transcription apparatus (reverse transcriptase, RNA and primer) and the ability to direct endogenous cDNA synthesis. Labelled particle cDNA hybridized strongly to human genomic DNA but not to mouse and cat DNA, thus indicating the human origin of the T47D particles. Furthermore all human DNAs, hybridized with the labelled particle cDNA, showed a uniform hybridization pattern of restriction fragments, indicating the endogenous origin and distribution of the proviral particle DNA in the human genome.